THE INFLUENCE OF COMPOSITION OF CNT (CARBON NANOTUBE) ON THE PHYSICAL PROPERTIES OF BIOPLASTIC MADE FROM CASSAVA STARCH - Masitoh Mangsur; Akbar Hanif Dawam Abdullah; Rahmat Firman Septiyanto; Yus Rama Denny Muchtar; Isriyanti Affifah (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2019)
Bioplastics are starch-based polymers that are easily degraded by microorganisms, so they can be used as an alternative to the use of conventional plastics. In this research, bioplastics made from cassava starch was made using glycerol as plasticizer and used MWCNTs (Multi-Wall CNTs) type CNT as reinforcement with variations in the composition of 0%, 1%, 2%, and 3%. Bioplastics are made with a dry method (dry blending) with stages of pre-mixing, mixing, hot press and cold press. Characteristics of bioplastic starch/CNT include tensile strength, biodegradation and morphological. The test results show that the addition of CNT composition affects the mechanical properties of bioplastics. The optimum value of tensile strength occurred in the addition of 2% CNT at 13.52 MPa. Biodegradable test results using the Aspergillus niger mushroom prove that bioplastic starch/CNT can be degraded well. The results of morphological characteristics in the form of SEM results showed that 3% bioplastic starch / CNT had cracks and resulted in decreased tensile strength. FTIR test results indicate the presence of a new functional group C≡C because of the addition of CNT.